Reference Walking Speeds for Healthy Young Adults in Qatar: Moderating Effect of Obesity and Physical Activity - Lina Majed (7485380) (2022)
Walking speed (WS) is considered an important indicator for overall health. Despite this, there is a paucity of data relating to WS values in the Arab region. The present study aims to establish preferred (PWS) and maximal walking speeds (MWS) in young adults in Qatar and examine how gender, body mass index, and physical activity (PA) components influence WS. One hundred ninety-six healthy participants (age: 22 ± 2 years; 60% females) performed a standardized walking test on a flat 10-m pathway, completed the short form of the International PA Questionnaire, and had their height and weight measured. PWS and MWS were normalized for height (rPWS and rMWS). Results. Females demonstrated slower PWS, MWS, and rMWS compared to males. Moreover, MWS and rMWS were lower in obese participants compared to underweight, normal weight and overweight individuals. There was a significant positive relationship only between vigorous PA and rPWS and rMWS. This is the first study to establish reference WS values for healthy young adults in Qatar. Overall, we demonstrated that WS was lower compared to similar adults worldwide. The established healthy walking values can serve as reference for clinical evaluations within Qatar. Future PA guidelines and public health interventions should focus on WS values. Other Information Published in: Sage Open License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/21582440221079919